Warda - Ibrāhīm, Ṣunʻ Allāh (Margellos world republic of letters book., 2021)
Sonallah Ibrahim's 2000 masterpiece offers readers a view of twentieth-century world events through the diary pages of his titular character 1950s Cairo. At a leftist meeting, idealistic journalist Rushdy encounters the enchanting Warda, along with her older brother Yaarib. Years later, after Warda goes mysteriously missing, Rushdy immerses himself in her diaries in a quest to uncover her whereabouts. The quest takes him to the bucolic, remote region of Dhofar, Oman, where he discovers Warda's guerrilla role in a regional revolt and secret involvement in revolutions with echoes around the globe, from the march against the Vietnam War in Washington, D.C., to the trial of Angela Davis and the actions of George H.W. Bush. Piece by revelatory piece, Rushdy uncovers the truth about Warda--and the fiery commitment that drove her to choose the life she lived. Widely acknowledged as a masterpiece by one of Egypt's most important novelists, this is an unforgettable story of intrigue, passion, and revolution.